Exposure to cigarette smoke precipitates simple hepatosteatosis to NASH in high-fat diet fed mice by inducing oxidative stress. Issue 17 (17th September 2021) - Fouda, Sherouk; Khan, Anwar; Chan, Stanley M.H.; Mahzari, Ali; Zhou, Xiu; Qin, Cheng Xue; Vlahos, Ross; Ye, Ji-Ming
Abstract: Consumption of diet rich in fat and cigarette smoking (CS) are independent risk factors of non-alcoholic steatohepatitis (NASH), and they often occur together in some populations. The present study investigated the mechanisms of high-fat diet (HFD) and CS, individually and in combination, on the pathogenesis of NASH in mice. C57BL/6 male mice were subjected to either a low-fat chow (CH) or HFD with or without mainstream CS-exposure (4 cigarettes/day, 5 days/ week for 14 weeks). HFD alone caused hepatosteatosis (2.5-fold increase in TG content) and a significant increase in 3-nitrotyrisine (by ∼40-fold) but without an indication of liver injury, inflammation or fibrosis. CS alone in CH-fed mice increased in Tnfα expression and macrophage infiltration by 2-fold and relatively less increase in 3-nitrotyrosine (18-fold). Combination of HFD and CS precipitated hepatosteatosis to NASH reflected by exacerbated makers of liver inflammation and fibrosis which were associated with much severe liver oxidative stress (90-fold increase in 3-nitrotyrisine along with 6-fold increase in carbonylated proteins and 56% increase in lipid oxidations). Further studies were performed to administer the antioxidant tempol to CS exposed HFD mice and the results showed that the inhibition of liver oxidative stress prevented inflammatory and fibrotic changes in liver despite persisting hepatosteatosis. Our findings suggest that oxidative stress is a key mechanism underlying CS-promoted progression of simple hepatosteatosis to NASH. Targeting hepatic oxidative stress may be a viable strategy in halting the progression of metabolic associated fatty liver disease.